Vers une géographie expérientielle à l’école : l’exemple de l’espace proche - Caroline Leininger-Frézal; Sophie Gaujal; Catherine Heitz; Pierre Colin (Recherches en Éducation)
Our research was born from the observation of the students' relationship to their close space. Indeed, they have personal experience of their space but do not articulate it with academic knowledge. The field of didactics thus allows us to explore in the form of collaborative research and to test in the field an experiential approach to teaching the geography of the near space that we have modeled. This appeared to be a relevant pedagogical lever to allow the articulation between a spontaneous geography and a reasoned geography inherent in the school geography in renewal. This experiential geography thus allows the student to think differently about his or her immediate space, to give meaning to the learning carried out, to construct a geographically narrative and thus to be part of a conscious citizenship.